2020
DOI: 10.2105/ajph.2019.305389
|View full text |Cite
|
Sign up to set email alerts
|

Is Insurance a Barrier to HIV Preexposure Prophylaxis? Clarifying the Issue

Abstract: Clinical trials have demonstrated that preexposure prophylaxis (PrEP) protects against HIV infection; yet, even with its approval by the Food and Drug Administration (FDA) in 2012, less than 10% of eligible users in the United States are currently taking PrEP. While there are multiple factors that influence PrEP uptake and pose barriers to PrEP implementation, here we focus on PrEP’s cost in the United States, which, at the current list price of $2000 per month and with high levels of cost sharing, can leave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 20 publications
3
59
0
Order By: Relevance
“…Access and cost are key known barriers to PrEP in the United States, Europe, and Australia [ 5 , 6 ]. Additionally, UNAIDS has indicated that having PrEP in a select group of centers is a barrier to PrEP service delivery due to the long distances to these facilities and attendant transport costs [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Access and cost are key known barriers to PrEP in the United States, Europe, and Australia [ 5 , 6 ]. Additionally, UNAIDS has indicated that having PrEP in a select group of centers is a barrier to PrEP service delivery due to the long distances to these facilities and attendant transport costs [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…PrEP is currently being implemented globally with varying degrees of interest among MARPs. Acceptability of PrEP in the United States, Europe, and Australia has been high among MSM, despite access and cost barriers [ 5 , 6 ]. Data on PrEP acceptability in sub-Saharan Africa are limited; however, a few studies have shown high acceptability among MSM [ 7 , 8 ] and variable acceptability and adherence among adolescent girls and young women [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, many existing PrEP navigation services support individuals in initiating PrEP (e.g., providing information on accessing medication assistance programs, answering questions about using PrEP, disseminating information on where to access PrEP, accompanying individuals to initial PrEP medical visit). This service should be expanded to include PrEP retention efforts after initiation, as some of the barriers or challenges to starting PrEP are the same for remaining on PrEP (e.g., lack or lapse of insurance, cost, side effects) [40][41][42][43]. Case management, which has been shown to be effective in managing HIV care, is another option to support PrEP users [44][45][46].…”
Section: A Need For Prep Support Servicesmentioning
confidence: 99%
“…7,8 While ensuring adequate health insurance is not an explicit part of the federal government's Ending the HIV Epidemic, 9 health insurance has impacts on access to HIV care, 10 access to ART, 11,12 achievement of viral suppression, [13][14][15] and access to PrEP. 16 Access to HIV care and viral suppression are associated with improved morbidity and mortality for the individual. 17,18 For PLWH, insurance has also been associated with a survival benefit.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] For those at increased risk for HIV, lack of health insurance is a barrier to PrEP access. 16 In addition, lack of health insurance has been associated with delayed PrEP initiation despite available patient assistance programs and any delay in initiation can result in preventable HIV infections. 23 Moreover, PrEP-related out-of-pocket costs can vary widely depending on one's insurance, 24 and high PrEP-related costs are a barrier to PrEP use.…”
Section: Introductionmentioning
confidence: 99%